Transformer Oil Quality Monitoring Towards Degradation of Insulation Breakdown Voltage - Maleiva, Lalak Tarbiyatun Nasyin; Ningsih, Melly Mulya; Kusumawardhani, Eka; Putra, Leonardus Sandy Ade; Nugraheni, Putranty Widha (Eksergi, 2022)
The transformer is one of the critical pieces of equipment for distributing electrical energy from the generator connected to the transmission to the consumer of Diesel and Gas Power Generation Service Units (ULPLTD/G). Therefore, the existence of insulation is essential due to its function as a separator among the transformer core and as a transformer cooler to minimize the heat that arises in the transformer. Hence, the objective of this research was to evaluate the transformer oil quality. The procedure was executed by observing the transformer and collecting data directly from the diesel machine of SWD 2, SWD 3, and SLZ 5. The results revealed that the breakdown voltage of transformer oil categorized as good was SLZ 5 oil with an average of 59,983, and the less good was SWD 2 oil with an average of 34.516. Furthermore, by observing the test results for new and used transformer oil, the breakdown voltage value for new transformer oil was always higher than used oil. Eventually, the transformer efficiency achieved was 95.58%.